Penerapan model discovery learning untuk meningkatkan kemampuan pemecahan masalah matematis siswa MTs kelas VIII - Sifa Salamah; M. Afrilianto; Tina Rosyana (IKIP Siliwangi, 2024)
The purpose of this study was to determine the increase in mathematical problem solving abilities of students who received the discovery learning model with students who received ordinary learning. The research method used was quasi-experimental. The population in this study were students of class VIII MTs Al-Furqon located in Cisarua, West Bandung with samples taken as many as two classes. The experimental class received learning by applying the discovery learning model, while the control class received ordinary learning. Data collection techniques by giving pretests and posttests. Quantitative data processing techniques were processed using MS Excel and SPSS. The results showed that students had the ability to solve mathematical problems when they learned to apply the discovery learning model.